Healing with water : English spas and the water cure, 1840-1960 - Adams, Jane M. (Manchester University Press, 2015)
'Healing with Water' provides a medical and social history of English spas and hydropathic centres from 1840 to 1960. It investigates health practices and healing cultures at specialist inland resorts showing that water was used in varied therapeutic approaches by both orthodox and unorthodox practitioners.